Foot and Mouth Disease in Indonesia and International Trade Policy; What Can Be Learnt from The Recent Outbreak? - AK, M Daud; Aiyub Kadir, M. Yakub; Humaira, Nabyla; Kurniasari, Eka (Jurnal Veteriner, 2024)
The statement letter from the World Health Agency " Office Internationale Des Epizoties  (OIE)," started in OIE Resolution Number XI in 1990, has been a new independence for Indonesia to rebuild the livestock and animal health sector. However, the outbreak of foot and mouth disease (FMD) in mid-May 2022 in Indonesia and the Central Asian country of Kazakhstan in early January 2022 proves that the importance of the role and influence of international trade, both formal and informal trade, directly or indirectly on government policies in exporting animals and its products to prevent the spread of FMD disease through commodity trading. In addition, the lack of supervision of trade in animal commodities and animal products from export and import activities will impact the emergence of other new infectious diseases that will occur in the future. Therefore, world health organizations, international trade organizations, and governments must review policies related to international trade to prevent repeated transmission and other new diseases in the future by evaluating the causes of FMD transmission in countries declared free of FMD, such as Indonesia. This paper attempts to analyze this problem through the history of FMD in Indonesia and the FMD-free zone from the perspective of international trade. This paper can provide information and contribute to the future prevention of FMD through international trade in Indonesia.